Expression of Six Peptidases from Lactobacillus helveticus in Lactococcus lactis - Luoma, Susanna (American Society for Microbiology, 2001)
For development of novel starter strains with improved proteolytic properties, the ability of Lactococcus lactis to produce Lactobacillus helveticus aminopeptidase N (PepN), aminopeptidase C (PepC), X-prolyl dipeptidyl aminopeptidase (PepX), proline iminopeptidase (PepI), prolinase (PepR), and dipeptidase (PepD) was studied by introducing the genes encoding these enzymes into L. lactis MG1363 and its derivatives. According to Northern analyses and enzyme activity measurements, the L. helveticus aminopeptidase genes pepN, pepC, and pepX are expressed under the control of their own promoters in L. lactis. The highest expression level, using a low-copy-number vector, was obtained with the L. helveticus pepN gene, which resulted in a 25-fold increase in PepN activity compared to that of wild-type L. lactis. The L. helveticus pepI gene, residing as a third gene in an operon in its host, was expressed in L. lactis under the control of the L. helveticus pepX promoter. The genetic background of the L. lactis derivatives tested did not affect the expression level of any of the L. helveticus peptidases studied. However, the growth medium used affected both the recombinant peptidase profiles in transformant strains and the resident peptidase activities. The levels of expression of the L. helveticus pepD and pepR clones under the control of their own promoters were below the detection limit in L. lactis. However, substantial amounts of recombinant pepD and PepR activities were obtained in L. lactis when pepD and pepR were expressed under the control of the inducible lactococcal nisA promoter at an optimized nisin concentration.